A pair of Schiff base enantiomers studied by absorption, fluorescence, electronic and vibrational circular dichroism spectroscopies and density functional theory calculation1. Issue 46 (23rd May 2015) - Tang, Hui-Hui; Zhang, Lu; Zeng, Li-Li; Fang, Xue-Ming; Lin, Li-Rong; Zhang, Hui
<x xml:space="preserve">Abstract</x> A pair of enantiomeric Schiff bases were synthesized and characterized, in particular their absolute configurations were determined by vibrational circular dichroism spectroscopy.